Incomplete freezing strategies for achieving long-lasting preservation of muscle foods: categories, regulations, efficiencies and challenges - Zichun Jin; Chaoping Jiang; Bingkun Sun; Jialin Liu; Wenxiu Sun (Food Science of Animal Products)
The modern development of commercial circulation has forced the preservation of muscle foods to achieve technology innovation and transformation. Incomplete freezing is a promising technology for muscle food preservation, which can be used as a compromise strategy between traditional chilling and freezing. It can not only inhibit microorganism and enzymatic activity with a cooler environment, but also avoid the severe drip loss triggered by the generous ice crystals, thus maintaining a stable quality in the storage, transportation and consumption. However, confusing nomenclature and blurred boundary appeared in the related researches is fatal to the standardization system formation and future development. To provide a clear reference, the review describes the moisture/ice-crystal behavior succession during cooling stage of muscle foods, and takes it as guideline to classify incomplete freezing techniques into 4 categories: superchilling (from 0 °C to freezing point), micro-freezing (from freezing point to 2 °C below freezing point), partial freezing (from 2 °C below freezing point to phase-transition endpoint) and sub-freezing (from phase-transition endpoint to –18 °C). As reported, the shelf life of muscle foods could be extended by 1.4–8 times under vaious incomplete freezing compared to traditional chilling. Meaningful regulatory approaches (cryoprotectant, packaging, physical field, etc.) were also highlighted, which could further enhance the practical effects of incomplete freezing by inhibiting vital deterioration factors such as microbial growth, oxidative reactions and ice crystal formation. Finally, refinement, real-time, industrialization and digitization as main challenges were presented to provide valuable references for the future development of muscle food cold chain circulation based on incomplete freezing.